2021
DOI: 10.1002/csc2.20610
|View full text |Cite
|
Sign up to set email alerts
|

Dormancy attributes in sunflower achenes (Helianthus annuusL.): I. Intraspecific variability

Abstract: Cultivated sunflowers (Helianthus annuus L.) display variable degrees of achene dormancy at harvest and persistence during storage, interfering with high-quality hybrid seed production. Information on intraspecific variability for dormancy among cultivated sunflowers is scarce and was the subject of this work. A set of 21 sunflower genotypes of diverse origins (18 crop and 3 wild) was used for phenotyping dormancy traits. Experimental data included achene and embryo germination at different incubation temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…A decrease in ABA responsiveness in accordance to a lower dormancy level as a result of variation in the environmental conditions explored by seeds during their development and maturation has been previously reported in other species (Benech-Arnold et al, 1991, 1995Contreras, 2007) and suggested for sunflower (Bodrone et al, 2017). In addition, embryo sensitivity to ABA was also related to changes in achene dormancy level during dry storage, as was observed in Arata et al (2021) and reported previously by Le Page-Degivry et al (1996) and Rodríguez et al (2018). Thus, embryo responsiveness to ABA appears as a major factor controlling achene dormancy and appears to be regulated not only by the maternal environment and after-ripening time, but also reflects intraspecific variability, as shown in Arata et al (2021).…”
Section: Crop Sciencesupporting
confidence: 78%
See 4 more Smart Citations
“…A decrease in ABA responsiveness in accordance to a lower dormancy level as a result of variation in the environmental conditions explored by seeds during their development and maturation has been previously reported in other species (Benech-Arnold et al, 1991, 1995Contreras, 2007) and suggested for sunflower (Bodrone et al, 2017). In addition, embryo sensitivity to ABA was also related to changes in achene dormancy level during dry storage, as was observed in Arata et al (2021) and reported previously by Le Page-Degivry et al (1996) and Rodríguez et al (2018). Thus, embryo responsiveness to ABA appears as a major factor controlling achene dormancy and appears to be regulated not only by the maternal environment and after-ripening time, but also reflects intraspecific variability, as shown in Arata et al (2021).…”
Section: Crop Sciencesupporting
confidence: 78%
“…For LMA and BAR (wild genotypes), germination values were lower at 25 than 10 ˚C and remained below 30% in both sowing dates even after 150 d of storage. These wild genotypes exhibit strong thermo-inhibition, as shown in Arata et al (2021).…”
Section: Cluster Analysis: Experiments Imentioning
confidence: 88%
See 3 more Smart Citations